Aspects of Social Division Of Labour - Rakauskas, Juozas (Problemos, 1969)
The tradition which considers problems of social division of labour to be entirely economic should be defined more precisely. Social division of labour in the capacity of definite social “mechanism” which fixes the man to a special activity comprises not only economic but other aspects of social relations and therefore should be investigated in sociologic terms as well. Discrimination between its economic and sociologic problems protects both against distortion of the essence of social division of labour and of sciences studying it.